Calculation of the Molière radius for various configurations of an electromagnetic sampling calorimeter ECaL SPD NICA - Kovtun, V.E.; Malykhina, T.V. (Вопросы атомной науки и техники, 2021)
One of the main tasks of the electromagnetic calorimetry of the SPD setup is effective π⁰-γ separation in the energy range from 50 MeV to 10 GeV. Therefore, the current task is to optimize the design of the module cells in order to improve the physical parameters of the ECaL calorimeter. The Molière radius is determined in this work by the Monte Carlo method using Geant4 toolkit for various cell configurations of the calorimeter module. The results obtained in this work will be taken into account in the further development of the detecting systems of the ECaL SPD NICA.